Students’ Perception Towards the Implementation of the HyFlex Learning Model in the English Department - Putriani, Putriani; Amin, Fatimah Hidayahni; Luhriyani, Seny (Journal of Excellence in English Language Education, 2025)
This research aims to understand students' perceptions of the HyFlex learning model. The method used was descriptive qualitative to describe the research subject. Data were collected through observation, questionnaire distribution, and interviews. The results showed that most students in the English department of Universitas Negeri Makassar support the HyFlex learning model, which provides significant flexibility in accessing materials and participating in class. There are several reasons underlying students' support for this model, among others: flexibility of access, increased engagement, customized learning experiences, technological adaptation, and adjustment to individual needs. In addition, the HyFlex model also requires several supporting aspects, namely: learner flexibility, flexible learning design, supporting technology, effective classroom management, fair evaluation, supportive physical infrastructure and technology, flexible lecturer engagement, commitment to collaboration and interaction